Developing Indonesian Vocabulary Through the Application of the Mind Mapping Method in Children (Journal of Basic Education Research, 2024)
Purpose of the study: This study aims to investigate the effectiveness of implementing the mind map method in improving the Indonesian language vocabulary skills of children in Group B at Kindergarten School Al Khairiyah Kota Bandar Lampung. Methodology: This research uses qualitative methods with classroom action research as the main tool to teach Indonesian vocabulary to 19 group B children at Al Khairiyah Kindergarten, Bandar Lampung City with total sampling. Data collection, namely observation, documentation and analysis, was carried out to assess the impact of the method on vocabulary acquisition. Main Findings: In Cycle 1, the mind map method was applied in two meetings with a focus on the theme of food and drink, resulting in an increase in Indonesian vocabulary. Cycle 2 continued this approach with improvements to the clothing theme lesson, which resulted in significant improvements in students' understanding and response to the material. Overall, the application of mind map method proved effective in improving the Indonesian vocabulary skills of Group B children at Al Khairiyah Kindergarten, Bandar Lampung City. Novelty/Originality of this study: This study contributes to the field by demonstrating the effectiveness of the mind map method in improving vocabulary acquisition among young learners. This research is offers practical insights for educators seeking innovative approaches to language teaching and learning, which have the potential to advance pedagogical practices in early childhood education.